Excessive Pressure in the Subsurface Layer in a Crystal - Karasevskii, A.I.; Lubashenko, V.V. (Металлофизика и новейшие технологии, 2015)
As shown, the formation of surface of a semi-infinite crystal is accompanied with excessive pressure arising inside the subsurface region, resulting in changes of structural and phase states of this region.